Fundamentals of copy and layout - Book, Albert C.; Schick, C. Dennis (Lincolnwood, Ill. : National Textbook Company, 1997)
Creative philosophies. Copy: Researching the Ad, preparing to write, writing the Ad, the headline, copyediting, copyfitting. Layout: elements, materials, illustrations, organization of the Ad, typography, the finished product. Print media: newspapers, classified, consumer magazines, business publications, direct mail, out-of-home media, promotional products/specialty advertising, yellow pages advertising. Broadcast and interactive media: radio, television, internet advertising. Conclusion: cases.
Keywords: Advertising; Typography; Copy; Advertising copy; Advertising layout and typography